The Effect of Trust in the Intention to Use m-banking - Fernanda Leão Ramos; Jorge Brantes Ferreira; Angilberto Sabino de Freitas; Juliana Werneck Rodrigues (BBR: Brazilian Business Review)
Despite the alleged benefits of m-banking, its acceptance has been short of industry expectations. One plausible explanation may be consumers' initial lack of trust in available services. The objective of the study is to investigate the effect of trust in the intention to use m-banking in the Brazilian context, specifically among users of the city of Rio de Janeiro. Therefore, we developed and tested a model that relates trust and its antecedents (familiarity, ease of use, perceived usefulness, safety, privacy and innovativeness) with the intention to use m-banking. We got a sample of 272 users of financial mobile apps and through structural equation modeling the hypotheses were tested. The results confirmed most of the proposed hypotheses, and we found significant relationships between the construct trust and other constructs, which significantly influence the intended use of banking services via m-banking.